The Dynamics of Individual Investment Decisions: Evidence From The Dhaka and Chittagong Stock Exchange, Bangladesh - Awlad Hosen Sagar,; Mustafizur Rahman Sharon, (Asian Journal of Accounting Perspectives, 2023)
Research aim: Behavioural finance plays an analogous role to fundamental and technical analyses for investment decisions in the stock market. It deals with various factors that manipulate investment decisions. This study explores the factors influencing individual investment decisions in the Dhaka and Chittagong Stock Exchange (DSE and CSE) of Bangladesh. Design/Methodology/Approach: Based on existing finance theories and literature, several factors were included in the self-developed questionnaire, with data collected using random sampling. We used SPSS (Version 26) to analyse the primary data collected. In the questionnaire, there were 24 variables, and statistical analysis (multiple regression) was carried out. Research finding: There were 24 variables, five of which (i.e., investor experience, impact of P/E ratio, impact of fundamental analysis, impact of securities and brokerage firm, and impact of investor psychology) had significant impact on individual investment decisions in the CSE and DSE. Theoretical contribution/ Originality: Theories pertaining to individual investment decisions are based on individual judgment, sentiment, risk perception, and risk attitude. These mechanisms are associated with behavioural finance. Various behavioural finance studies have been conducted in developed countries, but not in developing countries like Bangladesh. As such, the dynamics of the investment decision are the main focus of the present study. Practitioner/ Policy implication: This article can serve as input to investment decisions that have an impact on economic value at the firm, industry, and macroeconomic level. Moreover, it highlights the role of related stakeholders and extent to which they influence investment decisions. Research limitation: This study is country-specific, and the number of respondents is limited to 125 only. We could not consider the impact of technological advancement during this period.